Medicinal plants and animals of an important seasonal dry forest in Brazil - Albuquerque, Ulysses Paulino; Brito, Alanne Lucena; Nascimento, André Luiz Borba; Oliveira, Antonio Fernando Morais; Quixabeira, Carla Mirele Tabósa; Dias, Diógenes de Queiroz; Lira, Eduardo Carvalho; Silva, Flávia Santos; Delmondes, Gyllyandeson de Araújo; Coutinho, Henrique Douglas Melo; Barbosa, Mariana Oliveira; Landell, Melissa Fontes; et al. (Ethnobiology and Conservation, 2020)
Research performed in recent years indicates that efforts are still needed to understand the advances in the Caatinga, an important dry seasonal forest, and identify its potential for bioprospecting. These efforts are also important for pinpointing the challenges that should be addressed in future research focused on identifying new candidates for pharmacological studies in this complex region. Thus, in this article, we present the main advances of studies on plants and medicinal animals in the Caatinga region and their implications for ethnopharmacology, and we then discuss future challenges to promote the search for candidates with pharmacological potential. Based on an exploration of the available literature, we performed a critical reading of the available evidence to provide a good scenario on the studies in the region. We find that despite the large number of studies available, it is necessary to organize efforts to fill gaps in different areas of knowledge and optimize the search for new natural products.